EFEKTIVITAS PENEGAKAN HUKUM PIDANA TERHADAP PERUSAHAAN PERKEBUNANAN DALAM KASUS KEBAKARAN HUTAN DAN LAHAN DI WILAYAH PROVINSI RIAU - Lubis, Anwar Wijaya; ', Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Agricultural development and plantation has an important meaning in anattempt to improve the national economic growth as well as increase tarap the lives ofthe community .In literature environmental problems hidup-masalah the environmentcan be classified into the accompanied three forms of , pt pgn promised to supply areprone to air pollution of the living environment ( pollution ) , of land use have mistakenlytargeted ( land owns missue ) and is draining or for you never to end natural resources (natural resource depeletion ) .The development of the agricultural sector clovecommodities which were accompanied by the criminal deeds as meant stages as well asenvironmental instead took pleasure in unrighteousness was exactly like the combustionof forests and land areas is a manifestation of its a number of concrete the ineffectivenessof licensing requirements and regulations imposed regulation or not an undeveloped tobe carried out efficiently law enforcement will involve all stakeholders namely relating toenvironmentThe kind of research this can be grouped in the kind of research empirical law orsociological , because in this research writer directly did an experiment in most of thesurvey or place to which be researched in order to provide a picture in complete andclear about the problem in question .The research was conducted in an administrativeterritory riau .Of the source of data that is used , pt pgn promised to supply: primary andsecondary data .The technique of data collection during this research with theobservations , the objective of the interview , and the results of literature that.Keywords : Land and forest fir - Publicly-listed plantation company accountability- Environmental crime